The relationship between teachers’ personality trait and organizational commitment in Kelantan i-Think selected secondary schools / Nurul Iffah Noor Azman - Noor Azman, Nurul Iffah (2014)
The purpose of this study is to investigate the relationship between teachers’ personality traits and organizational commitment in Kelantan z-THINK selected secondary schools. The scope of this study involved the teachers at selected secondary with z-THINK programme in Kelantan. This study attempted to understand the personality traits of the teachers can be a factor towards the organizational commitment in secondary school. The instrument of the research of this study is questionnaire. Through this study, the outcome of the result indicates that all the big five personality traits were significant correlated to organizational commitment. However, openness to experience is most dominant in influencing the both organizational commitment (affective and continuance commitment). Therefore this study hopes that the result can be valued and used as reference to any institutions especially in education field to employ teachers. The significant of result and analysis belongs to the population or other party. Undoubtedly, there are relationship between teachers’ personality traits and organizational commitment, but the results show that personality only has a small effect on organizational commitment which means that there are several other factors that influence the organizational commitment.